KLHL1 Controls CaV3.2 Expression in DRG Neurons and Mechanical Sensitivity to Pain - Martínez-Hernández, Elizabeth; Zeglin, Alissa; Almazan, Erik; Perissinotti, Paula; He, Yungui; Koob, Michael; Martin, Jody L.; Piedras-Rentería, Erika S. (Frontiers in Molecular Neuroscience, 2020)
Dorsal root ganglion (DRG) neurons process pain signaling through specialized nociceptors located in their peripheral endings. It has long been established low voltage-activated (LVA) CaV3.2 calcium channels control neuronal excitability during sensory perception in these neurons. Silencing CaV3.2 activity with antisense RNA or genetic ablation results in anti-nociceptive, anti-hyperalgesic, and anti-allodynic effects. CaV3.2 channels are regulated by many proteins [1], including KLHL1, a neuronal actin-binding protein that stabilizes channel activity by recycling it back to the plasma membrane through the recycling endosome. We explored whether manipulation of KLHL1 levels and thereby function as a CaV3.2 modifier can modulate DRG excitability and mechanical pain transmission or sensitivity to pain. We first assessed the mechanical sensitivity threshold and DRG properties in the KLHL1 KO mouse model. KO DRG neurons exhibited smaller T-type current density compared to WT without significant changes in voltage dependence, as expected in the absence of its modulator. Western blot analysis confirmed CaV3.2 but not CaV3.1, CaV3.3, CaV2.1, or CaV2.2 protein levels were significantly decreased; and reduced neuron excitability and decreased pain sensitivity were also found in the KLHL1 KO model. Analogously, transient down-regulation of KLHL1 levels in WT mice with viral delivery of anti-KLHL1 shRNA also resulted in decreased pain sensitivity. These two experimental approaches confirm KLHL1 as a physiological modulator of excitability and pain sensitivity, providing a novel target to control peripheral pain.